(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Cultural heritage monuments are, to a large extent, public goods of collective consumption, and their preservation is in the public interest of the society as a whole. The benefits arising from the owner’s investment and resulting from the existence and the use of a cultural heritage monument are usually not ``consumed’’ solely by the owner, but, to a greater or lesser extent, by the whole society or a particular group. In the case of the renovation and remediation of cultural heritage buildings, the life-cycle costs are determined in the operational phase, before the intended renovation or remediation. They should be used to select an economically sustainable solution, with the maximum potential to preserve the cultural and historical value. The paper presents the application designed for the elaboration of plans for the renovation and remediation of cultural heritage monuments, developed in the form of a web interface. The application processes data at the level of individual structural elements. For faster and more comfortable users’ work, a database of type objects is used, which combines primary data from the level of structural elements.